Trustee Decision-Making in Theory and Practice. - Clark, G (NAPF, 2005)
The report focuses on a subset of scheme governance issues – those to do with the taking of decisions on investment strategy by trustee boards. The results of the research on this subject, which was identified in the Myners report as an area where improvement was needed, are set out in this report.